A Kromberg és Schubert Kft. logisztikai elemzése - Bedőcs Ingrid (2021)
During my studies, I was very interested in the lectures on logistics topics. It is mainly the planning of purchasing and production that concerns me the most. But I was also interested in warehousing. As a result of my compulsory 70-day traineeship in the logistics department of Kromberg and Schubert Ltd, I thought it was a good idea to write my final thesis on this subject. The title of my dissertation is Logistics Analysis of Kromberg and Schubert Ltd, which can cover a lot of dol- gos, as logistics is a rather broad concept. In my thesis, I mainly focused on the company's purchasing, planning and warehousing. I have listed the problems encountered and tried to make suggestions for solving them in the areas of purchasing, planning and warehousing. It became clear to me that the problems in the company in the areas of purchasing and warehousing are mainly caused by suppliers. With the help of the literature, I have described several approaches to logistics as a field. I have introduced the 7M and 9M principles in order to give a more comprehensive picture of what logistics is all about. I tested my hypotheses by using the methods of interviewing and observation. Of the 3 hypotheses I put forward, 2 were confirmed, while the third was rejected.